Affirmative action, social inclusion and tribal development in Odisha, India: Persistent issues and the way forward - Pothal, Siba Prasad (International journal of economic perspectives, 2025)
The main aim of this exploratory study is to examine the impact of affirmative action on social inclusion and development of tribal communities or Scheduled Tribes (STs) in the eastern Indian state of Odisha by critically analyzing their quality of life and level of living based on certain selected human development indicators such as level of literacy and education, income and consumption patterns, health and nutritional status, livelihood and employment patterns, and access to basic needs. Using secondary data from multiple credible sources such as National Sample Survey (NSS) reports, Census of India statistics, National Family Health Survey (NFHS) reports and Unified District Information System for Education Plus (U-DISE+) for analysis, the study finds a very poor quality of life among the tribal people despite the fact that the central and the state governments are keen to eliminate the worst forms of human deprivations through affirmative action and anti-discrimination policies. From an affirmative action perspective, it is argued in this research that such poor quality of life among the tribal people is mainly owing to their historically rooted social disadvantages and exclusion from the recent development paradigm. The study emphasizes on the need for proper implementation of affirmative action policies to redress such exclusion and concludes with suggestions on how practical policy options can improve the quality of life and well-being of the tribal people.